NON-MUSLIM PERCEPTION OF ISLAMIC BANK: IS RELIGIOSITY MORE IMPORTANT THAN LOCATION, PROMOTION, & PRODUCTS - M. Fuad Hadziq; Nina Ismiyanti (Universitas Airlangga, 2022)
From a societal perspective, religion is one variable that contributes to economic growth. Islamic banks' brand image remained limited to Muslims, not to other consumers worldwide. Therefore, the point of this study is to examine the impact of religiosity on non-Muslims' perceptions of Islamic banks when compared to internal characteristics such as location, advertising, and product. This research applies a quantitative approach, analyzing numerical data from non-Muslim community demographic descriptions. The causal and contributory relationships between variables are estimated. This research employed a route analysis approach”a questionnaire with a Likert scale was utilized in conjunction with in-depth interviews. The sample was selected from Palangka Raya, Central Kalimantan, a multi-ethnic, multi-cultural, and primarily multi-religious city with 370 non-Muslims. The analysis method used path analysis that helped by SPSS 17.0. The sample was selected using a mix of area sampling and convenience sampling. The findings indicated that religion had little influence and made a negligible contribution to non-Muslims' perceptions of Islamic banking. The marketing mix elements of location, promotion, and product have a more significant effect on how Islamic banks are perceived. Islamic banks are not widely perceived as being exclusively for Muslims. Religious considerations are not the primary element in choosing a bank. Non-Muslims are typical sensible buyers.